Teaching-service partnership in the unified health system: implementation of outpatient pharmacotherapeutical follow-up - Marlon Silva Tinoco; Luísa Duarte Nogueira; Mariana Linhares Pereira; Roberta Carvalho de Figueiredo; Ariane Garrocho de Faria; Thais Bueno Enes; Cristina Sanches; Máyra Rodrigues Fernandes; David Garcia Álvares Abreu; André Oliveira Baldoni (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
Background: The irrational medicine use is a public health problem and, in this context, the pharmacist assists in improving the use of drugs, reducing the risks of morbidity and mortality and the costs of pharmacotherapy. Data referring to the pharmacy service highlight the importance and the emerging need of insertion of this professional in the health teams. Objective: To describe the process of implementation of the Pharmacotherapeutical follow-up Service in a Multidisciplinary University Outpatient Unit (UOU) and the variables related to the evaluation of the structure and the process. Methods: It is an experience report with all the steps of an implantion process. The data were collected through our own forms through the Integrated Health System (SIS - "SistemaIntegrado de Saúde", in Portuguese Language) and the pharmacy follow-up records registered between November 2015 and November 2016. Results: In the 12 months of the implementation, 312 consultations were carried out, with the majority of the patients (67%) arriving at the service by referrals from the doctors who work in the UOU, followed by referrals for primary care (22%). Conclusions: The service was implemented with an adequate structure to the pharmaceutical follow-up process, and the teaching-service integration was important for its operation. Difficulties of recognition of the service by the population and by other health units of the municipality cause the referral flow to be below than the capacity of service attendance.